Does corruption impact on state budget: evidence of Southeast Asia countries with a focus on Vietnam - Nguyen Thuc Huong, Giang; Vu Hoa, Dat; Hong Van, Nguyen (Public Finance Quarterly, 2025)
Corruption, a pervasive issue in many countries, significantly undermines economic development and governmental efficiency. Corruption is measured by a corruption index such as the Corruption Perception Index (CPI) and the Control of Corruption Index (CCI). In Vietnam, the corruption index reflects the severity and prevalence of corrupt practices, which may impact various facets of the economy, including the state budget. This study aims to explore how corruption influences the Vietnamese state budget. Secondary data is collected from 2012 to 2022, a period of social and economic changes in Vietnam. The study finds that while higher corruption perceptions, as indicated by the Corruption Perceptions Index (CPI), are correlated with higher revenue collection, the Corruption Control Index (CCI) shows a significant relationship with expenditure. In Vietnam, corruption does not have a direct effect on both revenue and expenditure to GDP, while factors like foreign direct investment (FDI) and inflation play a more significant role in shaping government revenue and fiscal policy. The research contributes to the literature adding the mechanism of influences of corruption index to state budget revenue and expenditure and being the first study to investigate this impact in Vietnam. This country still has problems with corruption and budget management. The paper also provides practical implications in helping researchers and policymakers, especially those in developing and emerging countries to develop a deep understanding of the impact of corruption on the state budget, as a cause-and-effect relationship in society, and from that prepare a necessary measure to prevent corruption as well as CCI and CPI upgrade to maintain citizen's and businesses' trust in the socio-political system, thereby support to the well management of the state budget.